Why is there so much unemployment and inequality in Spain? - Espínola, José Ramón de (Razón y fe, 2018)
Unemployment and inequality in Spain, like it or not, are so universal that they reach us all. Why is Spain the country where unemployment has grown the most? Why has unemployment in Spain been fueled and how is it fixed on young people? Why does the most distinguished of our youth have to seek life outside our borders? This study offers us some of the keys to the imbalances in our productive and distributive system, which are affecting our social and political system so negatively.